2012
DOI: 10.1016/j.ajpath.2011.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Altered Angiogenesis in Caveolin-1 Gene–Deficient Mice Is Restored by Ablation of Endothelial Nitric Oxide Synthase

Abstract: Caveolin-1 is an essential structural protein of caveolae, specialized plasma membrane organelles highly abundant in endothelial cells, where they regulate multiple functions including angiogenesis. Caveolin-1 exerts a tonic inhibition of endothelial nitric oxide synthase (eNOS) activity. Accordingly, caveolin-1 gene-disrupted mice have enhanced eNOS activity as well as increased systemic nitric oxide (NO) levels. We hypothesized that excess eNOS activity, secondary to caveolin deficiency, would mediate the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 59 publications
1
27
0
1
Order By: Relevance
“…As knockout of caveolin-1 inhibits angiogenesis by impairing VEGFR2 compartmentation and by causing a detrimental deregulation of endothelial NO synthase, LXR activation may restrain angiogenesis by altering the physiological conditions of caveolin-1 expression and internalization, and possibly endothelial NO synthase activity. 38,39 Furthermore, as lipid rafts/caveolae are membrane microdomains harboring multiple signaling platforms, we cannot exclude that the effects of LXR activation may extend to other relevant receptors and pathways, such as those of fibroblast growth factor or transforming growth factor-β.…”
Section: Discussionmentioning
confidence: 99%
“…As knockout of caveolin-1 inhibits angiogenesis by impairing VEGFR2 compartmentation and by causing a detrimental deregulation of endothelial NO synthase, LXR activation may restrain angiogenesis by altering the physiological conditions of caveolin-1 expression and internalization, and possibly endothelial NO synthase activity. 38,39 Furthermore, as lipid rafts/caveolae are membrane microdomains harboring multiple signaling platforms, we cannot exclude that the effects of LXR activation may extend to other relevant receptors and pathways, such as those of fibroblast growth factor or transforming growth factor-β.…”
Section: Discussionmentioning
confidence: 99%
“…NO is a major player in VEGF-mediated angiogenesis, and eNOS is the major source of NO production in the endothelium. Inhibition of eNOS activity attenuates capillary morphogenesis in vitro and VEGF-mediated angiogenesis in vivo (26,39). Although iNOS is more efficient in NO production, it is generally associated with inflammatory conditions, and it is recognized as a marker of inflammation.…”
Section: L626 Pedf and Lung Endotheliummentioning
confidence: 99%
“…Outside of the eye, studies on the effect of caveolae on angiogenesis have been confounding with some studies suggesting that Cav-1 promotes angiogenesis (Chang et al, 2009; Sonveaux et al, 2004; Woodman et al, 2003) while others indicate anti-angiogenic activity (Bauer et al, 2005; Lin et al, 2007). A study using the corneal VEGF pocket assay in Cav-1 −/− mice showed that Cav-1 expression promotes VEGF-induced corneal angiogenesis (Morais et al, 2012). In these studies, Cav-1 −/− mice had a significantly blunted angiogenic response to VEGF.…”
Section: Caveolins/caveolae In Other Ocular Cellsmentioning
confidence: 99%